Assessment of immunogenicity and protection induced by COBRA HA vaccines formulated with Infectimune in young and elderly ferrets - Xiaojian Zhang; Matthew H. Thomas; Amanda Lynch; Hua Shi; Ted M. Ross (PLoS ONE, 2026)
Influenza viruses cause seasonal epidemics resulting in substantial morbidity and mortality, particularly in the elderly population. Although annual high-dose or adjuvanted influenza vaccines help maintain antibody titers in individuals aged 65 years and older, vaccine-mismatched strains, especially H3N2 influenza viruses, often lead to severe disease. Therefore, a universal influenza vaccine capable of eliciting broadly protective immunity in older individuals is urgently needed. Here, Computationally Optimized Broadly Reactive Antigen (COBRA) based H1 and H3 hemagglutinin (HA) vaccines formulated with the clinical-stage investigational immune modulator Infectimune were evaluated in pre-immune young (9 months) and elderly (50–71 months) ferrets to assess age-related differences in antibody responses. COBRA HA vaccination elicited robust H1- and H3- HA-specific antibody responses in both age groups. Following a single immunization, young ferrets developed significantly higher IgG titers than elderly ferrets, however, booster immunization with COBRA HA vaccines formulated with Infectimune increased anti-HA antibody titers in elderly animals to levels comparable to those of young ferrets. Upon influenza virus challenge, pre-immune young ferrets were largely protected against virally induced disease with minimal weight loss and reduced viral shedding, regardless if the ferrets were vaccinated with COBRA HA proteins or mock vaccinated. In contrast, only elderly ferrets receiving COBRA HA vaccines formulated with Infectimune were protected following challenge with significantly less body weight loss and lower nasal viral titers. These findings demonstrate that COBRA HA vaccines induce broad antibody responses in young and aged hosts and the addition of Infectimune enhanced vaccine efficacy in aged ferrets.